Challenging diagnosis of a rare disease: hypophosphatemic osteomalacia – case report and literature review - Nowak, Agnieszka; Partyka, Alicja; Pach, Magdalena; Dobrzańska, Justyna; Dziedzic, Mariola; Michalczewska, Aneta; Fugas, Agnieszka; Wierzejska, Natalia; Chmielowiec, Zuzanna; Smykiewicz, Karolina (Journal of Education, Health and Sport, 2024)
Hypophosphatemic osteomalacia is a rare condition caused by different causes, all resulting in disturbances of calcium-phosphate management. One of the most common causes among adults is tumor-induced osteomalacia, which is characterized by increased secretion of fibroblast growth factor-23. Its symptoms are vague, tests necessary for diagnosis are not commonly used by clinicians and some of them are only available in highly specialized centers. Due to these reasons, patients often are misdiagnosed for more common conditions and are left without proper treatment for many years. We present a case of a patient suffering from multiple fractures, diffuse bone pain, and muscle weakness, who was previously misdiagnosed for osteoporosis, primary and secondary hyperparathyroidism. We discuss the pathophysiology of tumor-induced osteomalacia, diagnostic path, differential diagnosis, available forms of treatment and possible complications.